Sediment Composition and Facies of Coral Reef Islands in the Spermonde Archipelago, Indonesia - Janßen, Alexander; Wizemann, André; Klicpera, André; Satari, Dewi Y.; Westphal, Hildegard; Mann, Thomas (Frontiers in Marine Science, 2017)
Sedimentological and geomorphological characteristics of coral reef islands are strongly related to past and recent boundary conditions such as the hydrodynamic regime, wind directions, sea-level fluctuations, and the ecological footprint of the surrounding reef complexes. Alterations in the physical, chemical and biological boundary controls may affect the stability of reef islands. Additionally, these factors are of importance in the context of future climate change. Such alterations through time may well be documented within the sedimentary record of reef islands and a better knowledge on its effects could help to improve our understanding of island responses to future changes of the status quo. However, detailed studies on the sedimentology and geomorphology of reef islands from southwest Sulawesi, Indonesia, are still rare. Here we report on the sedimentary composition and related facies zonation of four uninhabited coral reef islands in the Spermonde Archipelago. Sediment samples from onshore- and reef-flat environments were analyzed in regard to their grain size, component assemblages and facies distribution. Our results show that the analyzed island sediments are characterized by medium- to coarse-grained sand fractions and are well to poorly sorted. Across all islands examined, the surface sediment is predominately composed of materials identified as scleractinian coral and coralline red algae fragments, with minor additions from bivalves, gastropods and foraminifers. Importantly, statistical analyses of the variations in the percentage of these components allow for a clear sedimentary distinction of the four study sites into three outer shelf islands, situated closer to the open marine Makassar Strait, and one inner shelf island. On the inner shelf island, additional subsurface sedimentological analyses indicate a potential shift in major sediment contributors through time, preserved as coral-dominated accumulations within the subsurface samples, and coralline red algae-dominated deposits on top. These findings highlight the practical use of detailed sedimentological studies for the reconstruction of environmental changes in the Spermonde Archipelago.